Astaxanthin activated the SLC7A11/GPX4 pathway to inhibit ferroptosis and enhance autophagy, ameliorating dry eye disease - Hou, Chenting; Xiao, Jie; Wang, Youhai; Pan, Xinghui; Liu, Kangrui; Lu, Kang; Wang, Qing (Frontiers in Pharmacology, 2024)
Abstract：Dry eye disease (DED) is a common eye disease in clinical practice. The crucial pathogenesis of DED is that hyperosmolarity activates oxidative stress signaling pathways in corneal epithelial and immune cells and thus produce inflammatory molecules.The complex pathological changes of dry eye still need to be elucidated to facilitate treatment. In this study, we found that astaxanthin (AST) can protect DED through the SLC7A11/GPX4 pathway. After treatment with AST, the SLC7A11/GPX4 pathway was positively activated in DED both in vivo and in vitro accompanied by enhanced autophagy and decreased ferroptosis. In hyperosmolarity-induced DED corneal epithelial cells, AST increased expression of ferritin to promote iron storage and reduce Fe 2+ overload. It increased glutathione (GSH) and GPX4, scavenged ROS and lipid peroxide, rescued mitochondrial structure to prevent ferroptosis. Furthermore, inhibition of ferroptosis by ferrostatin-1 (Fer-1), iron chelator deferoxamine mesylate (DFO) or AST could activate healthy autophagic flux. Besides, in dry eye mouse model, AST upregulated SLC7A11 and GPX4 and inhibited ferroptosis. To sum up, we found that AST can ameliorate DED by reinforcing the SLC7A11/GPX4 pathway, which mainly affect oxidative stress, autophagy, and ferroptosis processes. ' 5'-GTGTCGCTGTTGAAGTCAGAGGAG-3'Mouse eye sections fixed with 4% paraformaldehyde in PBS for 15 min, then permeabilized with 0.5% Triton X-100 for 15 min, and blocked with 10% goat serum for 1 h. Samples were stained rabbit monoclonal anti-GPX4 antibody (1:250, Abmart) in antibody dilution buffer (Beyotime, Shanghai, China) at 4 °C overnight. Secondary staining was performed with Alexa FlourTM 488 goat anti-rabbit IgG (1:200, Invitrogen, USA) and Alexa FlourTM 555 goat anti-rabbit IgG (1:200, Invitrogen, USA) for 1 h at room temperature, and the nuclei counterstained with DAPI for 7 min.Intracellular Fe 2+ was assessed using treatment with 5 μM FeRhoNox-1 (Goryo Chemical, Inc., Sapporo, Japan) in Hank's balanced salt solution (HBSS; Thermo